2012
DOI: 10.1016/j.jvs.2012.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Murine ultrasound imaging for circumferential strain analyses in the angiotensin II abdominal aortic aneurysm model

Abstract: Objective The underlying causes of abdominal aortic aneurysms (AAAs) remain obscure, although research tools such as the angiotensin II (Ang II) apolipoprotein E-deficient (apoE−/−) mouse model have aided investigations. Longitudinal imaging and determination of biomechanical forces in this small-scale model have been difficult. We hypothesized that high-frequency ultrasound biomicroscopy combined with speckle-tracking analytical strategies can be used to define the role of circumferential mechanical strain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
2
26
1
Order By: Relevance
“…Thus, the increased resolution of the combined US-OCT approach allowed us to demarcate better the false lumen boundaries, even allowing detection of a small (0.08 mm 3 ) volume for M2 that was not visible on 3D US images but was evident with histology. This demarcation is in contrast to previous studies that have used US alone and have not been able to delineate the composition of the aortic wall or the inner and outer aortic diameters [7]. …”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…Thus, the increased resolution of the combined US-OCT approach allowed us to demarcate better the false lumen boundaries, even allowing detection of a small (0.08 mm 3 ) volume for M2 that was not visible on 3D US images but was evident with histology. This demarcation is in contrast to previous studies that have used US alone and have not been able to delineate the composition of the aortic wall or the inner and outer aortic diameters [7]. …”
Section: Resultscontrasting
confidence: 82%
“…Whereas the aforementioned studies focused on imaging-based models for computing normal hemodynamics, both US [7, 18] and MRI [1922] have also been used to assess lesion growth or wall strain in the AngII infusion model of dissecting aneurysms. Favreau et al [7] used high-frequency US alone, which did not allow them to “accurately differentiate between the intraluminal and extraluminal aortic wall.” To the best of our knowledge, only Ford et al [23] have built mouse-specific US imaging-based models of hemodynamics within such lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 We have previously presented a method to measure cyclic wall strains on the murine aortic wall to assess the changes in wall strain during aneurysm formation. 25 In this study, we translated our previously reported methods to assess strain in a murine model of IH.…”
Section: Discussionmentioning
confidence: 99%
“…23 In the current study, we hypothesized that there is a direct positive relationship between reduced cyclic arterial wall strain and the formation of intimal hyperplasia. To test this hypothesis, we combined a validated murine model of intimal hyperplasia 24 with a recently developed method for measuring arterial wall strains in vivo 25 to unravel the relationship between wall strain and neointima formation.…”
Section: Introductionmentioning
confidence: 99%